Different effects of two regeneration regimens on immunological parameters in cyclists - Meyer, T.; Faude, O.; Urhausen, A.; Scharhag, J.; Kindermann, W. (Medicine & Science in Sports & Exercise, 2004)
Purpose: To investigate the effect of 4-d active regeneration of different duration on immunological parameters after 2 wk of intensive training. Methods: In a cross-over design 11 male cyclists conducted 13 d of intensive training followed by 4 d of low-intensity cycling for either 1 or 3 h each day (sequence randomized). Before the intensive training (test 1), between training and regeneration (test 2), and after the regeneration period (test 3), subjects were tested in the lab: venous blood sampling (immunological parameters; flow cytometry) and incremental exercise stage test on a cycle ergometer. Results: Average values of lymphocytes and natural killer (NK) cells decreased significantly from test 1 to test 2 and were influenced differently by 1- and 3-h cycling (P = 0.018 and 0.039, respectively); 1-h cycling restored values from test 1, whereas 3 h led to a further decrease in lymphocyte and NK cell concentrations. This pattern was resembled by the courses of maximal heart rate and maximal blood lactate concentration during incremental cycling exercise. In leukocytes, tests 2 and 3 differed significantly from test 1 (P = 0.048 and 0.031, respectively), but there was no significant effect of the regeneration duration (P = 0.39). Neither the concentration of neutrophils nor the neutrophil oxidative burst was significantly influenced by the training period or by one of the regeneration phases. Conclusions: The present results indicate that low-intensity regenerative training sessions in cyclists should preferably be conducted for shorter durations than 3 h. It was demonstrated that 4-d cycling of 1 h each day reversed ergometric and immunological changes indicative of fatigue after 2 wk of intensive training.